2014
DOI: 10.1158/1538-7445.am2014-2620
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 2620: 3D multicellular pancreatic cancer spheroids as drug screening tool for pharmacological evaluation of EHT 5372 and other Mirk/DYRK1B inhibitors

Abstract: The dual-specificity tyrosine phosphorylated and regulated kinase Mirk/DYRK1B belongs to an evolutionary conserved family of kinases involved in the control of growth and development. DYRK1B has low level of expression in most normal cell types but is amplified or over-expressed in a number of human cancers. DYRK1B regulates the exit of cancer cells from quiescence through regulating cyclin D turnover and p27kip1 stabilization, thus participating as substantial actor in the control of cancer cell cycle progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…These results suggested that both compounds not only exhibited high potency in vitro but demonstrated also good activities in cell-based systems and in vivo models. These data therefore suggest a potential use of this class of inhibitors for targeting cancer cells with high DYRK1A/1B kinase activities. …”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…These results suggested that both compounds not only exhibited high potency in vitro but demonstrated also good activities in cell-based systems and in vivo models. These data therefore suggest a potential use of this class of inhibitors for targeting cancer cells with high DYRK1A/1B kinase activities. …”
Section: Discussionmentioning
confidence: 90%
“…Inhibitor 1 compared favorably to harmine, leucettine L41, and to the reactive and promiscuous compound epigallo-catechin-gallate EGCG In addition, it normalized Aβ-induced Tau phosphorylation in neuronal cells and also normalized DYRK1A-induced Aβ production in APP overexpressing cells . In addition, in vitro characterization in various cancer cellular models showed that the inhibitor targeted G0/G1 transition and reduced stemness and EMT properties of cancer cells organized in spheroids . Furthermore, it demonstrated promising activities in patient-derived ovarian cancer ascites spheroids and in vivo activities in a Panc1 xenograft model without detectable toxicity in mice .…”
Section: Discussionmentioning
confidence: 99%